Identification of mimotopes of human enterovirus 71 - Yee, Siew Fung. (Universiti Malaysia Sarawak, (UNIMAS), 2007)
A random phage-displayed peptide library was used to screen a raised rabbit serum antibodies against recombinant viral protien (VP)1 of B4 strain of human enterovirus (HEV)71 (R410 serum) for mimotopes of VP1 protein of HEV71.